Upaya Pembentukan Kepribadian Islami Santri Anak Usia Dini di Rumah Tahfidz Al-Fikri Kebun Bunga Permai Kota Palembang - Andini Sarina; Yanti Karmila Nengsih (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2022)
This study aims to describe efforts to establish Islamic personality for early childhood students at the Tahfidz Al-Fikri House, Permai Flower Garden, Palembang City. This type of research is descriptive with a qualitative approach, and data collection techniques are carried out by interview, observation and documentation methods. The subjects in this study were the chairman of the board of the Tahfidz Al-Fikri foundation, ustadz and ustadzah, parents of students and students. The results showed that the formation of the Islamic personality of early childhood students in Tahfidz Al-Fikri was carried out by instilling good Islamic Religious Education in students through several ways, namely providing value education, exercises, methods of giving examples (examples), and habituation methods. Through this method of forming an Islamic personality, the personality of early childhood students in Tahfidz Al-Fikri is formed, namely polite and obeying the rules, diligent, honest, time discipline and orderly learning, neat and clean, able to read, write hijayyah letters and memorize daily prayers, can carry out prayers, understand Islamic religious education, and are able to communicate well.